Sintesis, penambatan molekul, dan uji in vitro senyawa Benzimidazolvanilin dan turunan basa Mannich-nya sebagai anti-inlfamasi - Inas Priasti Siwi; Hayun; Arry Yanuar (Postgraduate, University of Mataram, 2024)
Benzimidazole and vanillin are compounds which can act as anti-inflammatory. However, the potential of these two compounds is still low. The structure of benzimidazole and vanillin was combined with Mannich base substitution in order to increase potency and selectivity as an anti-inflammatory. In this study, benzimidazolvanillin (1) and its Mannich base derivatives were synthesized. The synthesized compounds (2a-d) show anti-inflammatory activity based on in vitro tests by using protein denaturation inhibition test. Furthermore, the IC50 obtained ranged from 210 -243 μM. This potency is lower than diclofenac (IC50: 2,99μM). In molecular docking, the results of the inhibition constant ratio between COX-1 / COX-1 as well as the interaction of the ligand and target protein show that benzimimidazolvanillin and its Mannich-base derivatives could be anti-inflammatory drug candidates that should be investigated further.